Introduction to politics - Garner, Robert 1960-; Ferdinand, Peter; Lawson, Stephanie (Oxford University Press, 2016)
Bringing together theory, comparative politics, and international relations, Introduction to Politics reflects the realities of modern global politics. An accessible writing style, analytical approach, and a wide range of international examples to contextualise the content make it the perfect foundation for first year politics students